Heterotic affinity and combining ability of exotic maize inbred lines for resistance to aflatoxin accumulation - Meseka, S.; Williams, W.P.; Warburton, Marilyn L.; Brown, R.L.; Augusto, J.; Ortega Beltran, A.; Bandyopadhyay, Ranajit; Menkir, A. (Springer, 2018)
Aflatoxin accumulation in maize (Zea mays L.) kernels is a serious economic and health problem that reduces grain quality and nutritional values and causes death to livestock and humans. Understanding the genetic parameters and heterotic responses of exotic maize inbred lines can facilitate their use for developing aflatoxin resistant parents of hybrids in Africa. This study was designed to (1) determine the heterotic affinities of aflatoxin resistant exotic lines, (2) identify exotic inbreds with good combining ability, and (3) determine the mode of inheritance of resistance to aflatoxin contamination in these lines. A line × tester mating design was used to determine combining ability of 12 yellow and 13 white inbreds and classify them into heterotic groups. The inbreds were crossed to two adapted testers representing two African heterotic groups and the resulting testcrosses along with hybrid checks were evaluated in separate trials at two locations for 2 years in Nigeria. General combining ability (GCA) effects were more important than specific combining ability effects for aflatoxin and grain yield. Among 15 exotic inbred lines having negative GCA effects for aflatoxin and 13 with positive GCA effects for grain yield, six combined the two desired traits. Five white and six yellow endosperm testcrosses were found to be good specific combiners for the two desired traits. The exotic lines with negative GCA effects for aflatoxin accumulation will be used as donor parents to develop backcross populations for generating new inbred lines with much higher levels of resistance to aflatoxin accumulation.